REPRESENTATIVENESS OF THE TRANSLATION - Mardonov, Kuvonchbek (INTERNATIONAL CONFERENCES, 2022)
There are different types of translation. This article analyzes the types of translation, the specific characteristics and processes of translation types. In addition, scientific and theoretical views on this topic are summarized and recommendations are given.